Philippe Hugo and Adrian Schenker (eds.), Archaeology of the Books of Samuel. The Entangling of the Textual and Literary History (Supplements to Vetus Testamentum 132; Leiden: Brill, 2010). Pp. xx, 304. € 104.00 / US 154.00. ISBN 978-90-04-17957-8 - Dziadosz, Dariusz (The Biblical Annals, 2015)
Book review